1998
DOI: 10.1292/jvms.60.1341
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Listeria monocytogenes in Humans, Animals and Foods.

Abstract: ABSTRACT. The Listeria monocytogenes-carrying rates were 100% for listeriosis patients and 1.3% for healthy humans. The L. monocytogenes contamination rates for retail sliced beef (34.2%) and pork (36.4%) were significantly higher (p<0.05) than those for cattle (2.0%) and pigs (0.8%) and for cattle (4.9%) and swine (7.4%) carcasses. The percentages of serotypes 1/2a, 1/2b and 4b which are most dominant in human patients were high in isolates from fresh (90.0%) and processed (100%) fish and shellfish and import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 7 publications
1
32
0
3
Order By: Relevance
“…Isolation of L. monocytogenes from foods and animal stool samples has been reported in some countries [1]. A previous study reported isolation of L. monocytogenes from cow stools, carcasses and meat products, and suggested that feces was the most likely source of contamination of the carcasses [3]. The pathogen has also been isolated from environments such as slaughterhouses and sewage, sludge and food-processing plants [4,8,9].…”
mentioning
confidence: 99%
“…Isolation of L. monocytogenes from foods and animal stool samples has been reported in some countries [1]. A previous study reported isolation of L. monocytogenes from cow stools, carcasses and meat products, and suggested that feces was the most likely source of contamination of the carcasses [3]. The pathogen has also been isolated from environments such as slaughterhouses and sewage, sludge and food-processing plants [4,8,9].…”
mentioning
confidence: 99%
“…The infection, especially caused by Listeria monocytogenes, has been most frequently reported in cattle, sheep and goat, and less frequently in pigs and horses [8,15]. The pathogen has been isolated from healthy animals such as rats, cattle, dogs and pigs for reasons of public health concern [2,3,5,6]. There have been also some reports on the infection in wild animals, in over 30 species [4].…”
mentioning
confidence: 99%
“…Whereas, Listeria monocytogenes is often isolated from healthy animals [2,3] as well as natural environments, listeriosis is regarded as a opportunistic infection which requires certain predisposing factors. In this case, it is suspected that the canine distemper virus infection acted as a predisposing factor for listeriosis.…”
mentioning
confidence: 99%
“…A L. monocytogenes pode causar infecção localizada severa ou generalizada em humanos e em uma grande variedade de vertebrados domésticos ou selvagens (IIDA et al, 1998;VÁSQUEZ-BOLAND et al, 2001). As formas clínicas incluem infecção do útero gestante e aborto, septicemia com abscessos viscerais miliares e meningite e/ou encefalite (LECUIT, 2007;MAXIE & YOUSSEF, 2007).…”
Section: Listeriose Foi Identificada Em Quatro Porcos-daíndia (Cavia unclassified